L-5-hydroxytryptophan: antioxidant and anti-apoptotic principle of the intertidal sponge Hymeniacidon heliophila - Lysek, Nicola; Kinscherf, Ralf; Claus, Ralf; Lindel, Thomas (Zeitschrift für Naturforschung. C, a journal of biosciences, 2014)
The intertidal sponge Hymeniacidon heliophila which survives under intense sunlight contains the antioxidant amino acid l-5-hydroxytryptophan (ʟ-5-HTP) as major constituent. The content of ʟ-5-HTP was determined as (0.45 ± 0.23)% of the dry weight by quantitative NMR-spectroscopical analysis with an internal standard. Other known antioxidants such as flavonoids, carotenoids or tocopherol derivatives were absent. Both the oxidation potential and the concentration of ʟ-5-HTP in H. heliophila correspond to the values observed for flavonoids being major antioxidants in plants. It was shown that ʟ-5-HTP suppresses UVinduced apoptosis in human monocytes at the same concentrations as it occurs in the sponge tissue.